2011
DOI: 10.1007/s12303-011-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Diverse exhumation of the Mesozoic tectonic belt within the Yangtze Plate, China, determined by apatite fission-track thermochronology

Abstract: New and mostly published apatite fission-track (AFT) data are compiled to reveal the exhumation of the Mesozoic tectonic belt (MTB) within the Yangtze Plate, China. New AFT ages ranging from 51 ± 3 to 108 ± 5 Ma with mean measured track lengths between 11.8 ± 1.6 and 12.8 ± 2.0 µm, are obtained for the bedrock samples collected along a southeast to northwest transect across the MTB, including the exceptional Huangling Dome in the northern Yangtze Plate. The diverse, involving the first rapid, following by a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Therefore, we prefer to state that the lithospheric thinning of the YTC might have happened after 75 Ma. This is consistent with the observations of the recent thermochronological studies [ Li and Shan , ; Shen et al ., ], which have indicated that the rapid cooling and exhumation events occurred throughout the YTC after ~96 Ma.…”
Section: Implications For the Geodynamic Setting Of Eastern Asian Consupporting
confidence: 94%
“…Therefore, we prefer to state that the lithospheric thinning of the YTC might have happened after 75 Ma. This is consistent with the observations of the recent thermochronological studies [ Li and Shan , ; Shen et al ., ], which have indicated that the rapid cooling and exhumation events occurred throughout the YTC after ~96 Ma.…”
Section: Implications For the Geodynamic Setting Of Eastern Asian Consupporting
confidence: 94%
“…Denudation in the Sichuan Basin started at ~40 Ma by incision of the Yangtze River, and—likely—due to relief building across the eastern margin of the Tibetan Plateau [ Richardson et al, , ]. Studies along the northern and eastern margins of the Sichuan Basin [ Li et al , ; Deng et al , ] focused on the Hannan‐Micang [ Chang et al, ; Xu et al, ; Tian et al, ; Hu et al, ] and Huangling massifs [ Hu et al, a; Shen et al ., , ; Xiang et al, ; Xu et al, ; Li and Shan , ; Hu et al, ]. Integrated these data, Yang et al [] concluded that the eastward growth of the Tibetan Plateau has triggered exhumation of these massifs since ~13–8 Ma.…”
Section: Regional Low‐temperature Thermochronologymentioning
confidence: 99%
“…Low‐temperature thermochronological results have been reported from the core of the Huangling dome (Ge et al., 2013, 2016; S. Hu et al., 2006; X. Li & Shan, 2011; Liu et al., 2009; Richardson et al., 2010; C. B. Shen et al., 2009; C. H. Xu et al., 2010, 2013), the dome sides (Liu et al., 2009), and neighboring synclines (Yu et al., 2017). Published zircon and apatite fission track (ZFT and AFT) and helium (ZHe and AHe) ages, as well as the newly obtained ZHe ages in this study, are plotted in Figure 3.…”
Section: Geological Backgroundmentioning
confidence: 97%
“…During the past few decades, low‐temperature thermochronological methods have been extensively applied to explore the exhumation process of the crystalline basement in the dome core (e.g., Ge et al., 2013; S. Hu et al., 2006; X. Li & Shan, 2011; Liu et al., 2009; C. B. Shen et al., 2009; C. H. Xu et al., 2010; D. Xu et al., 2013). Inverse models integrating apatite and zircon (U–Th)/He and apatite fission track data reflect moderate cooling with rates of ∼1.9–2.7°C/Ma in the Late Jurassic and Early Cretaceous (Ge et al., 2013; Liu et al., 2009; C. B. Shen et al., 2009; C. H. Xu et al., 2010) or the Early to early Late Cretaceous (Ge et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation